Comparative analysis of time spent by the fire department on call of elderly victims fall in collective transport. - Blanco, Priscilla Hellen; Castilho, Mario Moreira; Silva, Eraldo Schunk; Cortez, Lucia Elaine Ranieri (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: The public transport is a major form of transportation in the cities and the increasing elderly population became many users this means of transport. Objective: The objective of the research was to compare the time spent by the fire department in the care of elderly fall victims in public transportation between two cities. Method: Data were collected by analyzing the database record of the overall occurrences of the fire department on the fall of elderly people in public transport in the cities of Curitiba and Maringá between the years 2005-2012. Collected were the region the city where the event occurred; hospitals for referral of victims and the time spent in attending these events by teams of firemen from the cities. Results: Increased occurrence of falls in the elderly collective transport four times in Maringá was observed. The frequency of these occurrences happened mainly in the central region in both cities and time attendance differed significantly and in Maringa most visits took place within an hour and Curitiba with over an hour. Conclusion: We conclude that further studies should be conducted and management strategies of public transportation employees so they can improve the time spent on mobile medical care.